Analisis Persepsi Multi-Stakeholder Tentang Penguatan Ekosistem Asuransi Kesehatan Berdasarkan Pojk Nomor 36 Tahun 2025 - I Made Indra Purwanita; Nike Septivani (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2026)
The health insurance industry in Indonesia is currently facing major challenges, including rising medical inflation, increasing claim ratios, healthcare fraud, and escalating healthcare costs that threaten the sustainability of health financing. To address these issues, the Financial Services Authority (OJK) issued Regulation Number 36 of 2025 concerning the Strengthening of the Health Insurance Ecosystem. The successful implementation of this regulation requires collaboration among all stakeholders involved in the health insurance ecosystem. This study aims to analyze multi-stakeholder perceptions regarding the implementation of OJK Regulation Number 36 of 2025 and to identify key factors supporting the strengthening of Indonesia's health insurance ecosystem. A qualitative descriptive approach was employed using purposive sampling. Informants consisted of representatives from BPJS Kesehatan, the Indonesian Life Insurance Association (AAJI), insurance practitioners, healthcare providers, and academics. Data were collected through in-depth interviews and document analysis, while qualitative data were analyzed using open coding, axial coding, and selective coding supported by source and method triangulation. The findings indicate that all stakeholder groups perceive the regulation positively. Good governance, stakeholder collaboration, digital transformation, risk management, and improved insurance literacy and human resource competencies were identified as the main determinants supporting effective implementation. The study proposes a conceptual model for strengthening the health insurance ecosystem and provides policy recommendations to support sustainable health insurance governance in Indonesia.